EFFECT OF CALCIUM SOAP SUPLEMENT ON RUMINAL METABOLISM AND FATTY ACID COMPOSITION OF LONGISIMUS MUSCLE IN LOCAL SHEEP - G. Joseph; A. Parakkasi; T. R. Muchtadi; R. Priyanto (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2018)
The experiment was carried out to study an effect of lipids in form of Ca-Soup which based on fish oil on ruminants. 15 local male sheep were devided into 3 treatments, namely: RA (basal diet without Ca-Soap) as control; RB (control diet + 5% Ca-Soap); and RC (control diet + 10% Ca-Soap). The basal diet was in pellet form which consisted of 40% field grass and 60% concentrate. The experiment design used was Randomised Block Design with 3 diet treatments and 5 replications. The results showed that the supplementation of Ca-Soap which using fish oil had significant effect on increasing of VFA total production, it could also improve the carcass quality and fatty acid ratio. Ca-Soap with fish oil base was effective as energy and polyunsaturated fatty acid sources in sheep diets. It was indicated by normal rumen metabolism and good performance.